A Semi‐Structured MODFLOW‐USG Model to Evaluate Local Water Sources to Wells for Decision Support. Issue 4 (12th January 2016) - Feinstein, Daniel T.; Fienen, Michael N.; Reeves, Howard W.; Langevin, Christian D.
Abstract: In order to better represent the configuration of the stream network and simulate local groundwater‐surface water interactions, a version of MODFLOW with refined spacing in the topmost layer was applied to a Lake Michigan Basin (LMB) regional groundwater‐flow model developed by the U.S. Geological. Regional MODFLOW models commonly use coarse grids over large areas; this coarse spacing precludes model application to local management issues (e.g., surface‐water depletion by wells) without recourse to labor‐intensive inset models. Implementation of an unstructured formulation within the MODFLOW framework (MODFLOW‐USG) allows application of regional models to address local problems. A "semi‐structured" approach (uniform lateral spacing within layers, different lateral spacing among layers) was tested using the LMB regional model. The parent 20‐layer model with uniform 5000‐foot (1524‐m) lateral spacing was converted to 4 layers with 500‐foot (152‐m) spacing in the top glacial (Quaternary) layer, where surface water features are located, overlying coarser resolution layers representing deeper deposits. This semi‐structured version of the LMB model reproduces regional flow conditions, whereas the finer resolution in the top layer improves the accuracy of the simulated response of surface water to shallow wells. One application of the semi‐structured LMB model is to provide statistical measures of the correlation between modeled inputs and the simulated amount of water that wells derive from local surface water. The relations identified in this paper serve as the basis for metamodels to predict (with uncertainty) surface‐water depletion in response to shallow pumping within and potentially beyond the modeled area, see Fienen et al. (2015a).